Impact of Conflict on Foreign Direct Investment and Socio-Economic Development: A 30-Year Analysis of Nigeria's Economy - Falana, Olatunbosun Ayo; Oladipo, Olaniyan Niyi; Adedun, Olalekan Ademola; Ogundele, James Segun (Acta Universitatis Danubius. Œconomica, 2023)
This study investigates the impact of conflict and insecurity on foreign direct investment (FDI) inflows and socio-economic development in Nigeria from 1983 to 2013. It explores the dynamics between Nigeria's economic growth, marked by becoming Africa's largest economy in 2014, and the challenges posed by decades of conflicts, using the theoretical framework of Conflict Theory. The research employs an ARDL bounds testing approach to analyze the relationships between FDI and key economic indicators, concluding that trade openness significantly attracts FDI, while conflict notably deters it. Despite the negative impact of conflict, the positive role of a larger GDP on FDI affirms the Size-of-Market Hypothesis, suggesting that Nigeria's market size continues to appeal to foreign investors. The study's findings have implications for policy, emphasizing the need for economic liberalization, political stability, and conflict resolution to foster a conducive investment environment. It highlights the necessity for investors to assess political risks and suggests further research into additional factors influencing FDI. Overall, the study underscores the importance of stability and growth-oriented policies for enhancing FDI inflows, contributing to the discourse on economic development in emerging economies.